Religious tourism as a tool for sustainability: the case of Cyprus - Varnavas, Andreas; Rodosthenous, Nicos; Vogazianos, Paris (My University, 2018)
The sustainable development of tourism is still a huge challenge. In this paper, we regard Cyprus's religious tourism as a special form of tourism that can enrich Cyprus' tourism products while providing a way to alleviate the adverse effects of mass tourism and support sustainability. Although evidence is provided in the literature about the role of religious tourism as an alternative form of tourism, no formal method has been incorporated into this role. The study investigated the determinants and prospects of religious tourism in Cyprus and how it is supported by local residents' understanding of the concept and prospects of religious tourism and its links to local traditions and culture. This is the first step in making relevant bodies and institutions aware of the integration of religious tourism into their overall strategic plan for sustainable tourism development. It also introduces future research directions.
Keywords: Byzantine music; Religious tourism; Seasonality; Sustainability